2021
DOI: 10.3390/biom11091280
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Two Novel CIL-102 Upregulations of ERP29 and FUMH to Inhibit the Migration and Invasiveness of Colorectal Cancer Cells by Using the Proteomic Approach

Abstract: CIL-102 (1-[4-(furo[2,3-b]quinolin-4-ylamino) phenyl]ethanone) is a major active agent of Camptotheca acuminata’s alkaloid derivative, and its anti-tumorigenic activity, a valuable biological property of the agent, has been reported in many types of cancer. In this study, we researched the novel CIL-102-induced protein for either the induction of cell apoptosis or the inhibition of cell migration/invasiveness in colorectal cancer cells (CRC) and their molecular mechanism. Firstly, our data showed that CIL-102 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Upregulation of ERP29 in breast cancer cells inhibits cell proliferation and invasion by upregulating E‐cadherin, cyclin‐dependent kinase inhibitor, and spleen tyrosine kinase; downregulating fibronectin, epidermal growth factor receptor, and plasminogen activator receptor; and attenuating the overall ERK cascade 32 . A previous study suggested that the inhibitory effects of CIL‐102, an alkaloid derivative, on the migration and invasion of colorectal cancer cells are abrogated by ERP29 knockdown through ROS, JNK, and p300/CBP pathways 14 . Overexpression of ERP29 prominently inhibits the proliferative capacity of gastric cancer cells and nullifies the epithelial‐mesenchymal transition process in gastric cancer by inhibiting ERK1/2 and AKT phosphorylation 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upregulation of ERP29 in breast cancer cells inhibits cell proliferation and invasion by upregulating E‐cadherin, cyclin‐dependent kinase inhibitor, and spleen tyrosine kinase; downregulating fibronectin, epidermal growth factor receptor, and plasminogen activator receptor; and attenuating the overall ERK cascade 32 . A previous study suggested that the inhibitory effects of CIL‐102, an alkaloid derivative, on the migration and invasion of colorectal cancer cells are abrogated by ERP29 knockdown through ROS, JNK, and p300/CBP pathways 14 . Overexpression of ERP29 prominently inhibits the proliferative capacity of gastric cancer cells and nullifies the epithelial‐mesenchymal transition process in gastric cancer by inhibiting ERK1/2 and AKT phosphorylation 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study revealed that ERP29 knockdown elevates the migratory and invasive abilities of gastric cancer cells 13 . It has been documented that ERP29 upregulation inhibits migration and invasion of colon cancer cells 14 . Moreover, ERP29 protein expression in androgen‐sensitive prostate cancer cells (LNCaP) is increased three‐fold by co‐treatment with dihydrotestosterone and EPI‐001 (a prostate cancer inhibitor), 15 suggesting that ERP29 may be an antitumor protein in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3-(4,5-Di-2-yl)-2,5-ditetrazoliu (MTT) was used for cell viability analysis to evaluate the cytotoxic effect, as previously described [ 24 ]. To observe cell morphology characteristic of apoptosis, 4,6-diamidino-2-phenylindole (DAPI)-stained cells were examined by fluorescence microscopy, as previously described [ 25 ]. Cell-cycle distribution was analyzed using flow cytometry, as previously described [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…MS spectra and MS/MS fragment ion mass were determined with a Bruker MALDI-TOF/TOF analyzer (Bruker Daltonics, Bremen, Germany), and all product ions were submitted to a computer database and analyzed with the MASCOT MS/MS ion search (Matrix Science Inc., MA, USA) using the SwissProt database (all entries). The Bruker operation system, namely flexControl Version 3.3 (Build 85) and flexAnalysis software, were used to create peak lists [21].…”
Section: Protein Identification By Mass Spectrometry (Ms)mentioning
confidence: 99%